Acquired Von Willebrand's Syndrome in Systemic Lupus Erythematosus. (4th December 2014) - Taveras Alam, Sara; Alexis, Karenza; Sridharan, Ashwin; Strakhan, Marianna; Elrafei, Tarek; Gralla, Richard J.; Reed, Louis J.
Abstract : Acquired von Willebrand syndrome (AVWS) is an uncommon, underdiagnosed, and heterogeneous disease which is increasingly recognized as a cause of bleeding diatheses. Systemic lupus erythematosus (SLE) is an infrequent cause of AVWS. Herein, we report a case of AVWS diagnosed during the initial presentation of SLE in a previously healthy young man with no family history of bleeding diathesis who presented with worsening epistaxis, gastrointestinal bleeding, and anasarca. He was found to have severe anemia and prolonged activated partial thromboplastin time (aPTT) with severely decreased levels of von Willebrand factor (VWF) measurements in addition to markedly decreased factor VIII levels. Further evaluation revealed nephrotic syndrome and interstitial lung disease due to SLE. He initially received combination therapy with intravenous immunoglobulin (IVIG) and von Willebrand factor/factor VIII concentrates without significant improvement. Treatment with steroids, cyclophosphamide, and rituximab was followed by clinical improvement evidenced by cessation of bleeding. The short follow-up did not allow us to definitely prove the therapeutic effect of immunosuppressive treatment on AVWS in SLE patients. This case adds to the literature supporting the relationship between AVWS and SLE and highlights the importance of combination therapy in the treatment of severe AVWS as well as the role of IVIG, cyclophosphamide, and rituximab in AVWS associated with SLE.